Goodwill and the Spirit of Market Capitalism (translated by A. Shevchuk) - Ronald P. Dore (Journal of Economic Sociology, 2010)
The paper deals with opportunities for making a market capitalism based on goodwill. The author demonstrates that economists exaggerate a role of self-interests for the market economy. While mutual long-term obligations, readiness to rely on goodwill and relational contracting may become a more successful tool for effective administration of the economy and improvement of the quality of life. In support of his major argument the author provides empirical observations of peculiar institutional arrangements in the Japanese economy. It is also pointed out that relational contracting based on goodwill exists in other countries and fosters important economic advantages